EFFORTS OF THE TEACHER'S ROLE TO OVERCOME DIFFICULTIES IN LEARNING TO READ STUDENTS IN GRADE 2 ELEMENTARY SCHOOLS - Indah Nurul Arishanti; Isna Ida Mardiyana; Astien Diena Koesmini; Rukmiyati Rukmiyati (Citra Dharma Cindekia, 2022)
The main problem in this study is the lack of students' reading skills, so it is necessary to analyze the difficulties that affect students' reading skills. This study aims to find out how the efforts of the teacher's role to overcome students' learning difficulties in grade 2 elementary schools. This research uses a qualitative approach and descriptive method. The subjects of this study were teachers and grade 2 students. Data collection in this study used interview and documentation techniques. Data analysis techniques used are data collection, data reduction, data presentation and conclusion. Based on the results of this study it can be concluded that the teacher's role in overcoming reading difficulties for grade 2 students is to provide special hours for students who experience reading difficulties during recess or school hours and lack of interest in reading, lack of tutoring and lack of assistance from families in the process of learning to read students. The implication of conducting this research is to motivate students to learn to read from any book.